Multiple sex chromosome system in penguins (Pygoscelis, Spheniscidae) - Gunski, Ricardo José; Delgado Cañedo, Andrés; Del Valle Garnero, Analía; Ledesma, Mario Angel; Coria, Nestor; Montalti, Diego; Degrandi, Tiago Marafiga (Comparative Cytogenetics, 2017)
Penguins are classified in the order Sphenisciformes into a single family, Spheniscidae. The genus Pygoscelis Wagler, 1832, is composed of three species, Pygoscelis antarcticus Forster, 1781, P. papua Forster, 1781 and P. adeliae Hombron & Jacquinot, 1841. In this work, the objective was to describe and to compare the karyotypes of Pygoscelis penguins contributing genetic information to Sphenisciformes. The metaphases were obtained by lymphocyte culture, and the diploid number and the C-banding pattern were determined. P. antarcticus has 2n = 92, P. papua 2n = 94 and P. adeliae exhibited 2n = 96 in males and 2n = 95 in females. The difference of diploid number in P. adeliae was identified as a multiple sex chromosome system where males have Z1Z1Z2Z2 and females Z1Z2W. The C-banding showed the presence of a heterochromatic block in the long arm of W chromosome and Z2 was almost entirely heterochromatic. The probable origin of a multiple system in P. adeliae was a translocation involving the W chromosome and the chromosome ancestral to Z2. The comparison made possible the identification of a high karyotype homology in Sphenisciformes which can be seen in the conservation of macrochromosomes and in the Z chromosome. The karyotypic divergences in Pygoscelis are restricted to the number of microchromosomes and W, which proved to be highly variable in size and morphology. The data presented in this work corroborate molecular phylogenetic proposals, supporting the monophyletic origin of penguins and intraspecific relations.